Sustainable innovations in digital twin technology: a systematic review about energy efficiency and indoor environment quality in built environment - Venkateswarlu, Natakarani; Sathiyamoorthy, Mahenthiran (Frontiers in Built Environment, 2025)
In the contemporary digital age, the built environment undergoes significant changes because of technological innovations that improve building management, optimize building efficiency, and enhance overall productivity. Digital Twin technology has emerged as an indispensable tool for enhancing indoor environmental quality and optimizing energy efficiency in existing buildings. This demonstrates its similarity to several SDGs, where digital twin technology is key to achieving many of them, especially those relevant to our research: 7. Affordable and clean energy; 3. Good health and wellbeing are the primary outcomes of our study; 9. Industry innovation and infrastructure are the focus of our methodology; and 11. Sustainable cities and communication, to which our research contributes. However, some challenges require further consideration. First, to assess the methods and tools used to monitor and represent environmental parameters. Second, to review previous studies on Digital Twin technology in the context of energy efficiency and indoor environmental quality. This study systematically examined 261 academic articles to address these challenges, identifying 17 relevant publications investigating Digital Twin for enhancing energy efficiency and indoor environmental quality in buildings. The research emphasizes Building Information Modeling, Internet of Things, and Big Data, which collectively improve the monitoring and management of physical assets through real-time data replication. Our research illustrates the need for a multidisciplinary framework to rigorously analyze Digital Twin applications, as a comprehensive understanding of the consequences of this technology requires the integration of different fields. The review emphasizes the confined application of sensors for monitoring the environment, the importance of residents subjective impressions, and the need for further comparative studies on energy use estimation methods. For future investigation, enhanced international collaboration is imperative to improve the scholarly exploration of Digital Twin related to this field. Finally, the built environment can benefit significantly from implementing Digital Twin technology. However, the challenges must be addressed before technology can achieve its full potential for creating sustainable and energy-efficient buildings.